PERANCANGAN SISTEM APLIKASI PERPUSTAKAAN PADA SDN TEGAL PARANG 03 PAGI - SALMAN ALFARISI (LPPM, 2014)
The purpose of the study is to determine what kind of system applications used in processing transaction data borrowing and returning library books in Tegal Parang SDN 03 Morning and obstacles faced in the implementation of the system. Moreover, the authors hope that the reader can understand the use of a particular application system transaction data borrowing and returning books that is done manually. The method used in this design is a method grounded (grounded research) is a research method based on the facts and using comparative analysis with the aim of holding generalisas iempiris, define concepts, to prove the theory, develop a theory, collection and analysis of data at the same time. During the study the authors found that the Library of SDN Tegal Parang 03 Am yet to have a system of computerized data processing applications that can help employees to work faster and more effectively. This is due to the lack of human resources knowledgeable about information systems. After doing some research, the author concludes that the Library of SDN Tegal Parang 03 Morning require a computerized system that can help the work of its employees. The author tries to create a system that uses the Library System Applications programming language Delphi 7. Keywords: Application System Design Library In Tegal Parang SDN 03.